Water selective MFI zeolite membranes for application in the Fischer Tropsch Synthesis - Sadat Rezai, Seyed Alireza (Department of Chemical Engineering, 2014)
Selective removal of water from the Fischer-Tropsch Synthesis (FTS) during reaction may allow the use of a cobalt catalyst with crystal size <6 nm hence increasing the catalyst activity. Zeolite membranes are a potential route to in-situ water removal due to their chemical and thermal stability under FTS reaction conditions. Zeolite membranes with a low Si/ Al ratio are hydrophilic. It has been hypothesised that reducing the Si/ Al ratio will result in increased water selectivity and permeance. It is also hypothesised that the separation process can be modelled using the MaxwellStefan (MS) formulation. MFI zeolite membranes were synthesised on a-alumina supports, of varying Si/ Al ratio. Two synthesis techniques were used: viz. with and without the assistance of structure directing agents. The membrane physical properties were characterised by SEM and XRD. Membrane quality was evaluated using n-hexane porosimetry. Single gas and mixture separations were carried out. A trans-membrane pressure gradient was applied in single gas measurements. Binary and ternary mixture separations were carried out using a model reaction mixture that approximates FTS conditions. This mixture was fed to a Wicke-Kallenbach cell. The total pressure on both sides of the membrane was equal, with a sweep gas applied to remove the permeate. Single gas permeation measurements on a blank support shows that viscous and knudsen flow are the dominant transport mechanisms in the support. A single gas permeation model for the zeolite membranes show that viscous and knudsen flow still dominate in pure component measurements. This due to the high flux through the zeolite films. During mixture separations viscous and knudsen flow are negligible as there is no pressure gradient. Comparing pure component and binary mixture separations the flux of hydrogen decreases by more than two orders of magnitude for the binary case. In the binary system water adsorption results in blockage of pores hence hydrogen permeance is reduced. Binary H20/H2 separation selectivity increases with decreasing Si/ Al ratio. Increasing temperature results in a decrease in this selectivity. Water adsorption decreases with increasing temperature hence hydrogen can permeate faster. With the addition of n-hexane as a third component, permeance of water and hydrogen decrease, however ternary H20/H2 separation selectivity increases. The Maxwell-Stefan model developed does not predict binary hydrogen permeation well. Permeance is much higher than predicted by the model possibly due to defects. Ternary hydrogen permeance is however more accurately predicted. Water and n-hexane permeances are predicted well by the model.